2005
DOI: 10.1111/j.1444-2906.2005.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Incentive for shifts in water management systems by shrimp culturists in southern Thailand

Abstract: Water management systems and other business situations of shrimp culturists were surveyed in two districts in southern Thailand. There were three types of water management systems in southern Thailand, namely closed, semiclosed and open systems, categorized by the frequency of exchange of pond water. Shrimp culturists in those districts tended to shift their system from the open system to the closed system of their own accord, and the average net income ratio decreased due to the change of water management sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Such environmental disturbances cause serious destruction of surrounding estuarine ecosystems as well as direct damage to shrimp culture such as disease outbreaks of cultured organisms. Closed aquaculture systems have become common in shrimp aquaculture because such methods can control disease outbreaks and environmental pollution more easily 2 . However, production costs of closed systems are much higher than those of open systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such environmental disturbances cause serious destruction of surrounding estuarine ecosystems as well as direct damage to shrimp culture such as disease outbreaks of cultured organisms. Closed aquaculture systems have become common in shrimp aquaculture because such methods can control disease outbreaks and environmental pollution more easily 2 . However, production costs of closed systems are much higher than those of open systems.…”
Section: Introductionmentioning
confidence: 99%
“…Closed aquaculture systems have become common in shrimp aquaculture because such methods can control disease outbreaks and environmental pollution more easily. 2 However, production costs of closed systems are much higher than those of open systems. Moreover, environmental problems still remain when waste water is discharged from such farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter, and subject to property rights and farmers' acceptance, modeling findings on the estimation of the difference in financial performance between the “BAU” scenario and alternatives involving the restoration of mangroves ecosystem services could help in defining a level of compensation to provide to aquaculturists. However, as yields, costs and revenues can vary widely between sites [50], [51], our data on aquaculturists' profits would need to be complemented by other data on costs and revenues to generate reliable estimates of the impacts of management scenarios on aquaculturists' profits at local, regional or national scales [50], [51].…”
Section: Discussionmentioning
confidence: 99%
“…Expert advice to growers is usually to limit water exchanges and improve the quality of effluents (35). A study of alternative water management systems showed that farmers would voluntarily switch to closed systems with lower short-term profits because of the longer-term benefits of more stable and predictable production (36). Reduced water exchange assists in disease prevention (37).…”
Section: Pondsmentioning
confidence: 99%